Factors Affecting Acute Pesticide Poisoning Farmers in Nenu Village Manggarai Regency - Kristina Melania Bey; Luh Putu Ruliati; Dominirsep Ovidius Dodo (Universitas Nusa Cendana, 2022)
Farmers often use pesticides to prevent pests and diseases that damage crops and disrupt agricultural yields. Improper use of pesticides can cause poisoning to farmers. This study aimed to determine what factors affect farmers' acute pesticide poisoning. This research was analytical survey research with a cross-sectional design. The research location was in Nenu Village, Cibal District, Manggarai Regency, with the research period from January to November 2020. The population in this study amounted to 106 people, with a total sample of 51 farmers, obtained by simple random technique. The dependent variable was acute pesticide poisoning, while the independent variables consisted of knowledge, application method, spraying frequency, and farmer's behavior. Data were analyzed using the chi-square test. The results showed that knowledge (p-value=0.038), pesticide application methods (p-value=0.017), and farmer behavior (p-value=0.019) related to acute pesticide poisoning. In contrast, spraying frequency does not relate to pesticide poisoning (p-value=0.574). Agricultural extension workers need to assist farmers in using pesticides according to the provisions. Through the public health center, the health service needs to conduct periodic blood checks on farmers to determine the level of pesticide poisoning.